Hipótese de incidência de ICMS sobre demanda de potências elétricas - Silva, Ralffo Vieira e (2009)
The distinction between electric power demand and electric energy is not prompt especially for jurists. In face of the difficulty to understand their concepts, physical systems analogous to electrical systems were called on. Such analogous systems have proved helpful by way of shedding light on the physical concepts of those two distinct electric resources. Only after these simple comparisons and the culminating of a real exemplification, one can estimate to have proposed the concept of Demand.The concept of Electric Power Demand, for expressing its characteristics, is comprehensive, being presented also by way of references to lawful diplomas in force such as Decree 41.019/57, Decree 62.724/68, Decree 1.586/85 and Resolution 456/2000 issued by National Agency of Electrical Energy (ANEEL). In order to make the grasping of this theme easy, mainly for those who are more knowledgeable about jurisprudence in comparison with their knowledge of energy, a section containing basic concepts of Tax Law was inserted as well as controversial arguments of specialists. In this section we go over the concepts of Incidence Assumption, Generator Factor, Calculation Basis, Aliquot, Tax payer, PIC and Tax Substitution. To have a better understanding of the discussion about the incidence of ICMS (Value Added Tax on Sales and Services) on the supply of electricity, a brief historical review of its evolution since Tax on Sales and Consignment Contracts is hereby drawn up. At this point we make it clear that by way of the vote of the Minister of the Federal Supreme Court (SCF) the non-incidence of ICMS only applies to the State where the electrical energy originates pursuant to Clause X of Paragraph 2nd of Article 115 of the Federal Constitution. Almost invariably, theorists have presented arguments on the lawfulness of ICMS internal calculations. At this point we go over a basis for calculation and methodology based on Mathematics and graphic resources. After the completion of the whole preparatory phase, to make the theme more receptive and to manifest a contrary standpoint, an analysis is carried out on the basis of lawful diplomas such as the Federal Constitution, decrees, and complementary laws to the ICM incidence hypothesis over the Electrical Power Demand. On this occasion the misinterpretation on the demand on the part of those theorists is shown. As fundamentals for the absence of the incidence hypothesis, the theorists comments on tax principles regarding electrical energy in a more immediate form are presented. From the advent of electrical energy industry onwards, one can infer that for all net industry a tax component in relation to infrastructure cannot be taxed by way of ICM . Therefore one appeals to a Complementary Law which excludes demand as a basis for calculation; such Complementary Law impedes that containers like those similar to energy transmitters are taxed by ICM . Another view contrary to the incidence of such taxation is shown as one demonstrates that the infrastructure constitutes itself an annexed real estate to which ICM cannot be levied, for not being applicable to estate properties. To finish off one can see that the Ministers of the Federal Supreme Court by way of their decisions have positioned themselves against the incidence, but for the application of an inadequate doctrine which leads to considering demand as merchandise. This assertion results from controversial votes of said Court which are not in harmony with the decisions that are contrary to those votes.